Structural dynamics in DCNQI salts and transition metal dichalcogenides studied by electron diffraction simulation - Olaoye, Olufemi Opeyemi (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.